Serum homocysteine and total antioxidant status in vitiligo: A case control study in indian population - Shikha Gupta; Paschal D'souza; Tapan Kumar Dhali; Sarika Arora (Wolters Kluwer Medknow Publications, 2016)
Background: Oxidative stress is considered as an initial pathogenic event in melanocyte destruction. These free radicals are scavenged by antioxidants, whose sum of activity in serum is measured by total antioxidant status (TAS). In addition, homocysteine (Hcy) may mediate melanocyte destruction via increased oxidative damage. However, previous studies investigating these parameters in vitiligo provide equivocal results. Aims: To study and compare serum Hcy and TAS levels in vitiligo patients with controls and also to correlate these parameters with the various disease characteristics. The present study further looked into any correlation between serum Hcy and TAS in vitiligo. Materials and Methods: A case control study was conducted on 82 vitiligo patients and 83 controls aged 18-45 years after excluding factors which could potentially alter serum Hcy or TAS levels. Disease characteristics were studied and blood samples were obtained for measuring serum Hcy and TAS levels. Results: TAS levels were lower in vitiligo patients than controls (1.79 ± 0.51 vs. 2.16 ± 0.63 mmol/L; P < 0.001) and had a negative correlation with disease activity (r = −0.410, P < 0.001). However, serum Hcy levels were comparable between vitiligo patients (18.68 ± 9.90 μmol/L) and controls (20.21 ± 13.39 μmol/L) (P = 0.406). No significant correlation was found between serum Hcy and serum TAS levels. Conclusions: Serum TAS may be further investigated to establish its role as biomarker for vitiligo since its levels also correlate with disease activity. However, serum Hcy may not be a reliable marker in Indian population probably because of differences in dietary habits.